Ethiopia Public Sector Reform Approach : Building the Developmental State - A Review and Assessment of the Ethiopian Approach to Public Sector Reform - World Bank (Washington, DC, 2013)
The objective of this report is to review and recommend improvements to Ethiopia's approach to public sector reform in order to advise the Government and executive institutions on the future of its public sector reform. The report also serves as a think piece for the World Bank, other partners, and policy makers. The report provides important basic information about the features of Ethiopia's public sector reform approach and reviews what worked well and what did not. It draws lessons from other countries' experience to help develop ideas and instruments of future public sector reforms in Ethiopia. Ethiopia's system of decentralization process has been credible in devolving power, improving governance and service delivery well as narrowing the per capital differences among Regional Governments and districts. The second phase of decentralization was 'big bang' and brought some gaps on addressing administrative and fiscal decentralization issues associated with: a) detailed clarity of expenditure and revenue assignments, b) shortage of skilled manpower and lack of incentive in remote areas and inadequate budget for recruitment , c) building local government specific purpose fiscal transfer, d) local government mandate on Public Sector Reform (PSR) and capacity building and e) transfers and f)decentralizing more decision making power to regional states on deciding financial resource for PSR and capacity building implementation. In an effort to link the incentive and pay mechanisms to performance in the civil service, the Ministry of Civil Service (MoCS) has prepared a draft incentive guideline and is waiting for its approval by the Council of Ministers; it is an important step to the way forward. In the future, the guideline has to reflect a systematic and comprehensive incentive and pay reform and performance mechanism and rolled out as it is a prerequisite to the PSR.